September girls - Madison, Bennett (New York : HarperTeen, 2013)
Vacationing in a sleepy beach town for the summer, Sam is pursued by hordes of blonde girls before falling in love with the unusual DeeDee, who compels him to uncover secrets about the community's ocean-dwelling inhabitants.
Keywords: Secrecy; Mermaids; Vacations; Love stories; Secrets; Love; Young adult fiction; Love stories